STRATEGI KOMUNIKASI POLITIK BADAN PENGAWAS PEMILIHAN UMUM SULAWESI UTARA DALAM MENANGGULANGI PENYEBARAN HOAX PADA PEMILIHAN UMUM TAHUN 2024 - Pangemanan, Johnly; Niode, Burhan; Boham, Putri (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to identify and analyze the political communication strategies used by the North Sulawesi Provincial Election Supervisory Agency in tackling the spread of hoaxes in the 2024 elections. In today's digital era, the dissemination of information is no longer limited by space and time, making the flow of news faster and wider. However, this condition also poses a new challenge, namely the rise of hoaxes or fake news that has the potential to disrupt the stability of the general election process. The North Sulawesi Bawaslu as an election supervisory institution has an important role in ensuring the integrity of elections through effective political communication strategies to overcome hoaxes. One of the main tasks of the General Election Supervisory Agency (Bawaslu) is to ensure that the election process runs honestly, fairly, and transparently. In this fast-paced digital information era, the spread of hoaxes or fake news is a serious threat that can disrupt the course of general elections. Therefore, tackling the spread of hoaxes is an integral part of Bawaslu's duties. This research is expected to provide valuable input for Bawaslu and other related parties in designing a more effective communication strategy in tackling hoaxes in the context of future elections.